Controlling the Specimen Surface Temperature During Irradiation With a Submillisecond Electron Beam Produced by a Plasma-Cathode Electron Source; IEEE Transactions on Plasma Science; Vol. 49, iss. 9 - Vorobjev M. S. Maksim Sergeevich; Koval T. V. Tamara Vasilievna; Shin V. Vladislav; Moskvin P. V. Pavel Vladimirovich; My Kim An Tran; Koval N. N. Nikolay Nikolaevich; Ashurova K. T. Kamila; Doroshkevich S. Yu. Sergey Yurjevich; Torba M. Maksim (2021, 2021)
Title screen